PENDIDIK DAN PEJUANG KHARISMATIK SPIRITUALIS (Kajian Sosio-Historis K.H.R. As`Ad Syamsul Arifin) - Sa'ad, Suadi (Program Studi Pendidikan Agama Islam, 2016)
SPIRITUALIST CHARISMATIC EDUCATOR AND FIGHTER (Sosio-Historic Study on K.H.R. As'ad Syamsul Arifin). This research aims at finding out how the portraits of an educator named K.H.R. As'ad Syamsul Arifin journey which full of spirituality value. In the implementation of the study, it focused more on the study of socio historical by using library approach. The sources of the data are in the form of primary and secondary data which is strengthening by conducting interviews with the informants. The results of this study shows a portrait of an educator and a figther's journey at once. Stage by stage, he developed the pesantren ancestral heritage and fix it in accordance with the situation and progress of the present education without leaving the old traditions. Some of the steps undertaken are included the establishment of SDI and SMPI, SMAI and SMEAI, Ma'had 'Ali came to the level of the Institute/college which the reputation cannot be denied. In the process, a spiritual education applied at Pesantren Sukorejo has pioneered the existing of social laboratory where the students, pupils, and university students can learn to be socialized.